Relationship Frequency Of Cariogenic Food Consumption With Dental Caries Rate In Class Ii Students Sdn Mojo Viii/227 Surabaya - Prasetyowati, Silvia; Benny Dwi Agusta Agung P; Ida Chairanna M (Journal Dental Health, 2023)
Dental caries is a multifactorial disease, covering the main factors of teeth, microorganisms, carbohydrates and time as additional factors. One of the factors causing the susceptibility of school-age children to dental caries is the habit of consuming foods that are sticky and contain sugar. The problem in this study is the high rate of dental caries in grade II students of SDN Mojo VIII/227 Surabaya. This study aims to determine the relationship between the frequency of cariogenic food consumption and the number of dental caries in grade II students at SDN Mojo VIII/227 Surabaya. This type of research is cross-sectional analytics. The sample in this study was 40 people, and it was taken by purposive sampling. The method of collecting its data uses a questionnaire. The analysis technique uses Kendall's test. The results of the study found that there was a significant relationship between the frequency of cariogenic food consumption and the number of dental caries in grade II students at SDN Mojo VIII / 227 Surabaya.